Coccomyxa sp.KJ extract affects the fate of T cells stimulated by toxic shock syndrome toxin‐1, a superantigen secreted by Staphylococcus aureus. (13th June 2022) - Ohshima, Shino; Komatsu, Satoko; Kashiwagi, Hirofumi; Goto, Yumiko; Ohno, Yusuke; Yamada, Soga; Kanno, Akiko; Shimizu, Tomoka; Seki, Toshiro; Yasuda, Atsushi; Kuno, Hitoshi; Kametani, Yoshie
Abstract: T cell stimulation by bacterial superantigens induces a cytokine storm. After T cell activation and inflammatory cytokine secretion, regulatory T cells (Treg) are produced to suppress the immune response. Coccomyxa sp.KJ (IPOD FERM BP‐22254), a green alga, is reported to regulate immune reactions. Therefore, we examined the effects of Coccomyxa sp.KJ extract (CE) on the superantigen‐induced immune response. When human peripheral blood mononuclear cells (PBMCs) were stimulated with toxic shock syndrome‐1 (TSST‐1) in the presence of CE, the number of activated T cells decreased moderately. Purified T cells stimulated in the presence of CE comprised more non‐proliferating cells than those stimulated in the absence of CE, whereas some T cells proliferated more quickly. The levels of activation markers on the stimulated T cells increased in the presence of CE. Most of the inflammatory cytokines did not change but IL‐1β, IL‐17, IL‐4, and IL‐13 secretion increased, whereas that of IL‐2, TNF‐α, and IL‐18 decreased. IL‐10 secretion was also decreased by CE treatment, suggesting that the immune response was not suppressed by Treg cells. CE enhanced the expression of stem cell‐like memory cell markers in T cells. These results suggest that CE can regulate the fate of T cells and can help to ameliorate superantigen‐induced T cell hyperactivation and immune suppression.